Fuzzy Logic and Soft Computing - Dedicated to the Centenary of the Birth of Lotfi A. Zadeh (1921-2017) (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The present book contains 14 papers accepted and published in the Special Issue of the MDPI Mathematics journal, entitled "Fuzzy Logic and Soft Computing – Dedicated to the Centenary of the Birth of Lotfi A. Zadeh (1921-2017)", which covers a wide range of topics connected to the theory and applications of fuzzy logic and soft computing. More precisely, these topics include: mathematical programming problems with coefficients and/or decision variables expressed by fuzzy numbers; soft computing methods in a fuzzy environment; fuzzy inner product spaces; M-hazy vector spaces; interval ranges of fuzzy sets; arithmetic operations of fuzzy sets; gradual numbers; Interval-valued fuzzy soft sets; interval-valued fuzzy soft topology; preference relationships; L-fuzzy sub-effect algebras; Fuzzy differential subordinations; m-polar fuzzy set in semigroups; practical use of the marks; the fuzzy logic approach for decision-making systems in management control; multigranulation rough sets; the multigranulation roughness of an intuitionistic fuzzy set; decision-making algorithms, etc. We hope that this book will be useful for those who work in the domains of fuzzy logic and soft computing or for those who want to familiarize themselves with the most advanced knowledge in the field of fuzzy mathematics.